2020
DOI: 10.1186/s13643-020-01381-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring prevention and mitigation strategies to reduce the health impacts of occupational exposure to wildfires for wildland firefighters and related personnel: protocol of a scoping study

Abstract: Background: With an increase in wildfire activity across the globe and growing numbers of personnel involved each year, it is necessary to explore the health impacts of occupational exposure to wildfires and the practices and policies that can be implemented to mitigate these effects. The aim of this work is to (1) identify the impact occupational exposure to wildfires has on health outcomes including physical, mental, and social wellbeing; (2) examine the characteristics and effectiveness of mitigation strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The protocol for this project has been previously published. 32 To align with public health guidelines on physical distancing during the COVID-19 pandemic, we did not conduct meetings with stakeholders to discuss research priorities as indicated in our original protocol. Instead, we conducted virtual semi-structured individual interviews with a sample of survey respondents to contextualise identified research priorities, and enable broad representation given COVID-19 public health guidelines on travel and the realities of the wildland fire season.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for this project has been previously published. 32 To align with public health guidelines on physical distancing during the COVID-19 pandemic, we did not conduct meetings with stakeholders to discuss research priorities as indicated in our original protocol. Instead, we conducted virtual semi-structured individual interviews with a sample of survey respondents to contextualise identified research priorities, and enable broad representation given COVID-19 public health guidelines on travel and the realities of the wildland fire season.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project to establish health research funding priorities for the British Columbia Wildfire Service (BCWS) based on gaps in literature and stakeholder priorities. The protocol for this project has been previously published 32. To align with public health guidelines on physical distancing during the COVID-19 pandemic, we did not conduct meetings with stakeholders to discuss research priorities as indicated in our original protocol.…”
Section: Methodsmentioning
confidence: 99%
“…34 A systematic review protocol set out plans to identify health impacts of wildfires on firefighters and ways to reduce their risks. 35 A review of health effects in children called for enhanced preparedness, prioritizing low-cost smoke sensors, masks, and air filtration, 36 while a review of Australia's Black Summer proposed monitoring preparedness indicators, including household smoke alarms, response time for fires, and numbers of firefighting personnel and aircraft. 14 A new comprehensive review of wildfire causality and health effects provides a useful summary of research to date.…”
Section: New Health and Wildfire Research In 2020mentioning
confidence: 99%
“…However, these individuals and companies may not be wellprepared to protect themselves or their employees in the face of new hazardous environments. Owners of facilities and public agencies responding to crises such as wildland fires, will need to assure that contractors and recruits are adequately trained and protected to be able to work safely (Koopmans et al, 2020). These cross-over issues are examples of how TWH and Employer Preparedness intersect with community emergency preparedness and response.…”
Section: Findings Applying Twh To Employer Preparednessmentioning
confidence: 99%